Assessment of miscarriage factors among Latinas who live in the U.S.: a cross-sectional study - Fernandez-Pineda, Madeline; McCabe, Brian E.; Cianelli, Rosina; Villegas, Natalia; Ferrer, Lilian; Peragallo Montano, Nilda (Frontiers in Global Women's Health, 2023)
Introduction Latinas in the US are underrepresented in miscarriage research, yet face several risk factors for having a miscarriage, including intimate partner violence, and increasing maternal age. Increased acculturation is associated to increased risk of intimate partner violence and adverse pregnancy outcomes among Latinas yet is also understudied in the realm of miscarriage. Thus, this study aimed to analyze and compare sociodemographic characteristics, health-related factors, intimate partner violence, and acculturation among Latinas with and without a history of miscarriage. Methods This study utilizes a cross-sectional design to analyze baseline data from a randomized clinical trial on the effectiveness of “Salud/Health, Educación/Education, Promoción/Promotion, y/and Autocuidado/Self-care” (SEPA), a human immunodeficiency virus risk reduction intervention for Latinas. Survey interviews were conducted in a private room at the University of Miami Hospital. Survey data analyzed include demographics, a bi-dimensional acculturation scale, a health and sexual health survey, and the hurt, insult, threaten, and scream tool. This study's sample was 296 Latinas, 18 to 50 years old, with and without a history of miscarriage. Data analyses included descriptive statistics, t-tests for continuous variables, negative binomial for counts, and chi-square for dichotomous or categorical variables. Results Most Latinas were Cuban (53%), lived in the U.S. an average of 8.4 years, had 13.7 years of education, and a monthly family income of $1,683.56. Latinas with history of miscarriage were significantly older, had more children, more pregnancies, and poorer self-rated health than Latinas without history of miscarriage. Although not significant, a high percentage of intimate partner violence (40%) and low levels of acculturation were reported. Discussion This study contributes new data about different characteristics of Latinas who have and have not experienced a miscarriage. Results can help identify Latinas at risk for miscarriage or its adverse-related outcomes and help develop public health policies focusing on preventing and managing miscarriage among Latinas. Further research is warranted to determine the role of intimate partner violence, acculturation, and self-rated health perceptions among Latinas who experience miscarriage. Certified nurse midwives are encouraged to provide Latinas with culturally tailored education on the importance of early prenatal care for optimal pregnancy outcomes.